LESSON STUDY TO IMPROVE STUDENT ENGLISH GRAMMAR MASTERY USING JIGSAW TECHNIQUE TO THE THIRD SEMESTER STUDENTS OF IKIP SILIWANGI - Acep Haryudin; Ningtyas Orilina Argawati (Indonesian EFL Journal, 2018)
The implementation of Lesson Study is aimed to improve students’ ability in mastering the teaching materials on English grammar, fostering creativity, improving critical thinking, and increasing ability to work both personally and in group. In implementing this lesson study, the researchers used jigsaw as a learning technique. This study was conducted in 3 cycles, in which each cycle consists of planning (Plan), implementation (do), and reflection (see). The results showed that there are good developments on students’ learning where the constraints that appear can be minimized. Students understand the function and word forms, they have high critical thinking or curiosity, and they have no difficulties in comprehending Grammar Formula. Moreover, the result also showed that students have high motivation in learning English and there was no gap between high-motivated and low-motivated students. Finally, after knowing what, why, and how Lesson Study was implemented, lecturers could consider the importance of applying lesson study in the learning process.Keyword: cooperative learning, grammmar mastery, jigsaw, learning technique, lesson study